Strategy for Strengthening Creative Economy Based on Digital Entrepreneurship Through the Pentahelix Model in Deli Serdang Regency (Case Study in Percut Sei Tuan District) - Dina Arfianti Siregar; Cut Nizma; Darwin S.H. Damanik (International Conference on Multidisciplinary Research, 2022)
The purpose of this research is to find out the obstacles faced by business actors in strengthening the creative economy and determine what strategies are most appropriate in strengthening the creative economy. This type of research is a qualitative research with 15 research informants. Through interactive data analysis with interview techniques and focus group discussions, information related to the object of research was obtained. The results of the study show that there are obstacles faced by business actors, namely the inability to sell products using digital technology due to lack of knowledge and understanding of digital entrepreneurship, limited raw materials, lack of business capital, the role of media in online marketing and promotion has not been maximized, collaboration is not optimal between academics, business, government, community and media. The best strategy that can be applied is a growth strategy through the role of the government which is enthusiastically hold digital entrepreneurship training to improve marketing skills of business actors and sales volume, actively make promotion via digital marketing that can reach a larger number of target audiences, improve product quality, increase motives and product characteristics through innovation and creativity, actively hold exhibitions and marketing events, and conduct optimal collaboration between academics, business, government, communiy and media. Keywords: creative, digital entrepreneurship, pentahelix model